ABUNDANCE OF FORAGE LICHENS FOR BOREAL CARIBOU IN THE BOREAL SHIELD ECOZONE OF SASKATCHEWAN - Greuel, Ruth Josephine 1990- (2018)
Several species of terricolous fruticose lichens are important as winter forage for a threatened species, boreal caribou (Rangifer tarandus caribou (Gmelin)), in the northern boreal forest of Saskatchewan, Canada. This area is part of the Boreal Shield Ecozone, and experiences very high rates of natural forest fire. Lichens grow very slowly and take decades to develop substantial cover and depth. To understand the development of caribou habitat after fire and the availability of forage lichens across the range, we gathered forest inventory data at 312 sites in a stratified random design across northern Saskatchewan during 3 years of surveys. We took the following measurements at each site: tree ring samples for stand age, measurements of basal area density, moisture regime and species composition of vascular plants, bryophytes and lichens. Destructive samples of lichen biomass were taken at 72 sites. From these destructive lichen samples I tested various types of allometric equations for both measures of cover and volume relative to biomass. Linear allometric equations provided estimates of stand-level biomass (kg/ha) for each of the common stand types using plot-based measurements of lichen cover and volume. I used boosted regression trees (BRTs) to construct decision tree ensembles to assess the relative influence on lichen abundance of several environmental variables. This provides an understanding of the controls on lichen abundance and further insight into the differences between accrual of percent cover (dispersal of lichens) and depth (development of the lichen thalli). The different drivers controlling each of these types of lichen growth have rarely been examined, and while other studies on lichen abundance select one measure, they are typically not both considered within one study. Time since fire was the most important variable controlling both lichen percent cover and volume. UTM northing and basal area density were also important, but to different degrees for each measure. These results are ...